Business rescue in the construction industry in South Africa - Stokes, Timothy (My University, 2017)
ABSTRACT The business rescue regime was introduced into South African law on 1 May 2011 and now, almost six years since its inception, very little research has been conducted on how business rescue practitioners are achieving success. This research seeks to firstly understand what business rescue practitioners consider as a successful business rescue process and secondly, flowing from this, the research seeks to identify the determinants of success of a statutory business rescue process in the construction industry in South Africa. 11 business rescue practitioners, some with financial backgrounds and others with legal backgrounds were interviewed in order to gather data. Of these participants, certain also had a background in liquidations. Semi-structured interviews were conducted whereafter categories and themes were identified which are discussed and analysed. The Companies Act defines the rescuing of a company as a process of restructuring in order to maximise the likelihood of the company continuing in existence on a solvent basis or, if this is not possible, providing a better return for creditors than what they would receive in a liquidation. While some of the respondents considered the so called wind-down business rescues, where all of the assets are sold and the proceeds thereof are distributed to creditors, much like a liquidation but in accordance with the latter part of the definition of rescue, to still be a successful business rescue, this research proves that a successful rescue should rather be viewed as a process that saves as many Public Interest Score points as possible (van den Steen, 2017). In other words there should be a focus on saving the business as a going concern. In striving to save the business, the second leg of the research sought to identify the determinants of a successful business rescue process in the construction industry in South Africa. In striving to save as many Public Interest Score Points as possible, the key determinants of success identified by this research are as follows:  Support from SARS and financial institutions  Employee buy-in  Post commencement finance  Sound financial management / control  Effective leadership  Effective constant communication  The ability to negotiate and reach consensus  Overcoming legislative challenges  Nature and extent of original causes of failure (reasonable prospect of rescue at the outset)  Early filing  Injecting skills  The right business rescue practitioner
M.B.A. Thesis
Keywords: Business failures, Bankruptcy, Construction industry -- South Africa.